Implementation Of Debt To Equity Swap As A Corporation Debt Restructuring Effort - Ilham Akbar (LEGAL BRIEF, 2022)
This study aims to analyze the regulation of debt to equity swaps as an effort to restructuring corporate debt (corporation debt restructuring) in Indonesia and its legal consequences, and legal protection for diluted shareholders who do not agree to holding a debt to equity swap scheme. The method used in this research is a descriptive analytical research with a normative type of research. The data collection technique used is library research and the data analysis technique is a qualitative, deductive-inductive method. The results of the analysis show that arrangements regarding Debt to Equity Swaps have been regulated in the legal system regulations in Indonesia, namely those in Article 35 paragraph (2) of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT); Government Regulation Number 15 of 1999 Concerning Certain Forms of Claims That Can Be Compensated for as Deposits in Shares; OJK Regulation (P.OJK) Number 36/POJK.03/2017 Concerning the Prudential Principle in Equity Participation Activities. The legal consequence arising from the existence of a Debt to Equity Swap in an effort to restructure corporate debt is the emergence of legal certainty related to efforts to save the finances of a company that implements a Debt to Equity Swap. The form of legal protection that can be provided is by raising a rights issue in shareholder matters.